Finnish study of intraoperative irrigation versus drain alone after evacuation of chronic subdural haematoma (FINISH): a study protocol for a multicentre randomised controlled trial. Issue 6 (21st June 2020) - Tommiska, Pihla; Raj, Rahul; Schwartz, Christoph; Kivisaari, Riku; Luostarinen, T; Satopää, Jarno; Taimela, Simo; Järvinen, Teppo; Ranstam, Jonas; Frantzen, Janek; Posti, Jussi; Luoto, Teemu M; et al.
Abstract : Introduction: Chronic subdural haematomas (CSDHs) are one of the most common neurosurgical conditions. The goal of surgery is to alleviate symptoms and minimise the risk of symptomatic recurrences. In the past, reoperation rates as high as 20%–30% were described for CSDH recurrences. However, following the introduction of subdural drainage, reoperation rates dropped to approximately 10%. The standard surgical technique includes burr-hole craniostomy, followed by intraoperative irrigation and placement of subdural drainage. Yet, the role of intraoperative irrigation has not been established. If there is no difference in recurrence rates between intraoperative irrigation and no irrigation, CSDH surgery could be carried out faster and more safely by omitting the step of irrigation. The aim of this multicentre randomised controlled trial is to study whether no intraoperative irrigation and subdural drainage results in non-inferior outcome compared with intraoperative irrigation and subdural drainage following burr-hole craniostomy of CSDH. Methods and analysis: This is a prospective, randomised, controlled, parallel group, non-inferiority multicentre trial comparing single burr-hole evacuation of CSDH with intraoperative irrigation and evacuation of CSDH without irrigation. In both groups, a passive subdural drain is used for 48 hours as a standard of treatment. The primary outcome is symptomatic CSDH recurrence requiring reoperation within 6 months. The predefined non-inferiority margin for the primary outcome is 7.5%. To achieve a 2.5% level of significance and 80% power, we will randomise 270 patients per group. Secondary outcomes include modified Rankin Scale, rate of mortality, duration of operation, length of hospital stay, adverse events and change in volume of CSDH. Ethics and dissemination: The study was approved by the institutional review board of the Helsinki and Uusimaa Hospital District (HUS/3035/2019 §238) and duly registered at ClinicalTrials.gov. We will disseminate the findings of this study through peer-reviewed publications and conference presentations. Trial registration number: NCT04203550